1995
DOI: 10.1002/bbpc.19950990306
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐Doppler Zeeman Spectroscopy of the CS2 Molecule

Abstract: The Zeeman splitting of rotational lines in the V system of CS2 were systematically studied, using a cw single mode frequency doubled dye laser with linear and circular polarization in a cold collimated molecular beam within a tunable magnetic field up to 0.2 Tesla. Two sources of magnetic moments of levels in the excited 1B2 state could be identified. First, a second order spin‐orbit spin‐rotational coupling to the spin components of the 3A2(3Δu) electronic state is responsible for the generated magnetic mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This was first observed by Habib et al 10 Our spectrum is, however, superior in both sensitivity and resolution, which allows the unambiguous assignment of M . This assignment and accordingly the interpretation of the Zeeman pattern differs from that proposed by Habib et al 11 as will be shown below.…”
Section: Analysis and Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…This was first observed by Habib et al 10 Our spectrum is, however, superior in both sensitivity and resolution, which allows the unambiguous assignment of M . This assignment and accordingly the interpretation of the Zeeman pattern differs from that proposed by Habib et al 11 as will be shown below.…”
Section: Analysis and Discussionmentioning
confidence: 61%
“…If the energy of the perturbed level 1 B 2 (vЈ;03M ) * is close to that of ͉ 3 A 2 (A 1 ϩB 1 )v 0 ;13M ͘ ͑this is the case proposed by Habib et al 11 ͒, the Zeeman interaction between the mixed level 1 B 2 (vЈ;03M ) * and ͉ 3 A 2 (A 1 ϩB 1 )v 0 ;13M ͘ is zero for M ϭ0 as can be seen from the formula S in Eq. ͑20͒.…”
Section: Analysis and Discussionmentioning
confidence: 61%
See 2 more Smart Citations